Teknik Double Tounging dalam Sonata for Flute and Piano Karya Francis Poulenc - Mr. MEI ARTANTO , SINGGIH SANJAYA, ERITA ROHANA SITORUS (Saraswati)
Double tounging is one of playing techniques on the flute which emphasizes on the use of a double tongue which have meaning movement of the tongue interchangeably between the front and back of the tongue. Setting the tongue movement which stable and orderly between the front and back of the tongue when blowing the flute be a key principal to produce a good quality of double tounging in producing sound. This technique is a technique commonly used in the flute especially in playing staccato articulation that fast-paced so as a flute player with a standard skilled of the intermediate level should be able to lord those techniques. Not a bit of repertoire can apply double tounging in play with it, such as the Sonata for flute and piano works of Francis Poulenc. In these works there are parts using the technique double tounging in play when mastering single tonguing have segregated to the maximum speed of the tongue movement. With patience, accuracy, use a good method and practicing regularly and effective be the primary key in mastering technique of double tounging correctly and well. Key words : Double tounging technique, sonata, Francis Poulenc.